Development of Teaching Materials for Writing Fantasy Story Texts Integrated with Character and Local Wisdom - Emelfa, Emelfa; Ramadhan, Syahrul (JOLLT Journal of Languages and Language Teaching, 2024)
This development research was conducted to overcome the limitations of teaching materials for writing fantasy story texts with character and local wisdom at SMP Negeri 4 Tambang. The right writing teaching materials can improve students’ understanding and writing skills, especially writing fantasy story texts. With the inclusion of character education and local wisdom in the fantasy story text, it can form character and local wisdom values as an effort to preserve their own regional culture. This study aims to describe the process and products of developing teaching materials for writing fantasy story texts with character and local wisdom that are valid, practical, and effective for students. The development model used is 4D which includes defining, designing, developing, and disseminating. The test subjects in this study were 31 students of SMP Negeri 4 Tambang and Indonesian language subject teachers in class VII. The theories used in this research are teaching materials, writing, fantasy story text, character and local wisdom, and fantasy story text with character and local wisdom. The results showed that the teaching materials for writing fantasy story texts with character and local wisdom were valid, practical, and effective. The validation results obtained 92.1% with a very valid category. Practicality by teachers and students obtained 92.5% and 86.4% with an average of 89.5% which included a very practical category. The effectiveness of teaching materials obtained a score of 90.2% on student activity, 88.9% on student learning attitudes, 89.4% on knowledge competency and 89.5% on skill competency.